Kinetics of Phenol Removal from Aqueous Solution by Adsorption onto Peanut Shell Acid-activated Carbon - Gonzo, Elio Emilio (2005)
A pseudo-second-order rate equation describing the kinetic adsorption of phenol onto peanut shell acid-activated carbon at different initial concentrations, carbon dosages and particle sizes has been developed. The adsorption kinetics were followed on the basis of the amount of phenol adsorbed at various time intervals at 22°C. The rate constant and the equilibrium adsorption capacity were calculated. From these parameters, empirical correlations for predicting the equilibrium adsorption capacity as a function of the C0/D ratio, and for estimating the rate constant as a function of the relation D/(C0 dp )0.5, were derived. This allowed a general rate expression for design purposes to be obtained which was valid for C0 /D ≤ 1.5. The operation line for each case studied was constructed and the equilibrium adsorption capacity obtained. A comparison was undertaken with the experimental adsorption isotherm as previously determined. The effect of the initial phenol concentration, the carbon dose and the particle size on the initial adsorption rate was also analyzed.